2021
DOI: 10.3390/ijerph18062901
|View full text |Cite
|
Sign up to set email alerts
|

Is Acceleration a Valid Proxy for Injury Risk in Minimal Damage Traffic Crashes? A Comparative Review of Volunteer, ADL and Real-World Studies

Abstract: Injury claims associated with minimal damage rear impact traffic crashes are often defended using a “biomechanical approach,” in which the occupant forces of the crash are compared to the forces of activities of daily living (ADLs), resulting in the conclusion that the risk of injury from the crash is the same as for ADLs. The purpose of the present investigation is to evaluate the scientific validity of the central operating premise of the biomechanical approach to injury causation; that occupant acceleration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Because the occupants in the vehicle are strapped to the vehicle, they are the ones who are affected by most of the impact forces and not the crumple zones of the vehicle. The authors in [33] showed that as many as 50% of people involved in low-speed vehicle collisions reported cervical spine pain. The main limitation in such cases is the lack of knowledge about the mechanisms of whiplash injury during low-speed collisions.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Because the occupants in the vehicle are strapped to the vehicle, they are the ones who are affected by most of the impact forces and not the crumple zones of the vehicle. The authors in [33] showed that as many as 50% of people involved in low-speed vehicle collisions reported cervical spine pain. The main limitation in such cases is the lack of knowledge about the mechanisms of whiplash injury during low-speed collisions.…”
Section: Research Backgroundmentioning
confidence: 99%